Quimivox mobile 2.0: desenvolvimento de ferramenta no ensino da tabela periódica e distribuição eletrônica aos deficientes visuais utilizando dispositivos móveis - OLIVEIRA, Alex Santos de (Universidade Federal do Pará, 2020)
Technological advancement has helped the integration of the visually impaired by increasing access to education. This paper presents a proposal to update the application Quimivox Mobile, developed for Android devices, which presents a tool accessible to the visually impaired, giving access to periodic table of chemical elements via synthesis of Voice and commanded by global gestures that do not require pointing to specific elements of the interface. In order to enable vident/visually impaired collaboration, the application also provides visual returns. In addition to the numerical and organizational information provided by the periodic table, the Quimivox Mobile provides several explanatory and qualitative information regarding the: family, period, classification and main uses of the element. The application also adds accessible information about the distribution of electrons in layers and energy sublevels, based on the Linus Pauling diagram and analyzing the data obtained through the evaluation of the application. Consequently, the visually impaired may have greater autonomy in the study of the periodic table and the electronic distribution of the chemical elements when using the new application. Thus, a better teaching and learning of chemistry becomes possible, with equality in the use of technologies with accessibility techniques using mobile devices with touch screen and open source operating system.